2017
DOI: 10.1186/s12891-017-1788-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a theory-based multicomponent intervention (Movement Coaching) on the promotion of total and domain-specific physical activity: a randomised controlled trial in low back pain patients

Abstract: BackgroundThe promotion of physical activity is a major field in rehabilitation and health promotion but evidence is lacking on what method or strategy works best. Ensuing from this research gap, the present study compared the effectiveness of a comprehensive theory based multicomponent intervention (Movement Coaching) to a low intensity intervention in low back pain patients.MethodsA monocenter randomized controlled trial with three measuring points (T0 = baseline, T1 = six month follow-up, T2 = twelve month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
0
23
0
1
Order By: Relevance
“…At six months follow-up (T1), 92 participants replied to the questionnaire [19,20]. There were no statistically significant differences in the characteristics of participants who replied and did not reply within the Movement Coaching intervention group (p > 0.05).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…At six months follow-up (T1), 92 participants replied to the questionnaire [19,20]. There were no statistically significant differences in the characteristics of participants who replied and did not reply within the Movement Coaching intervention group (p > 0.05).…”
Section: Resultsmentioning
confidence: 98%
“…The consort flow chart of the main study has already been published [19,20]. At baseline (T0) 201 participants were randomised in the Movement Coaching intervention group.…”
Section: Sample Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that at 6-month follow-up there were no statistically significant between-group differences in physical activity [45]. It seems face-to-face education or a booklet is not sufficient for enhancement of knowledge.…”
Section: Discussionmentioning
confidence: 98%